106k views
4 votes
Simplify the expression.
3g- 9+ 11g - 21
The simplified expression is

User Ausi
by
4.9k points

2 Answers

5 votes

Answer:

14g-30

You need to combine like terms.

User Roy Dictus
by
5.1k points
3 votes

Answer:

g = -0.8571428571

Explanation:

3g + -9 + 11g + 21 = 0

Reorder the terms:

-9 + 21 + 3g + 11g = 0

Combine like terms: -9 + 21 = 12

12 + 3g + 11g = 0

Combine like terms: 3g + 11g = 14g

12 + 14g = 0

Solving

12 + 14g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-12' to each side of the equation.

12 + -12 + 14g = 0 + -12

Combine like terms: 12 + -12 = 0

0 + 14g = 0 + -12

14g = 0 + -12

Combine like terms: 0 + -12 = -12

14g = -12

Divide each side by '14'.

g = -0.8571428571

Simplifying

g = -0.8571428571

User Ahmed Mostafa
by
4.6k points